El trabajo didáctico de los obstáculos, en el corazón de los aprendizajes científicos - Astolfi, Jean-Pierre (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
The great deal of preconceptions that have been collected in the past ye:ars by sience education researchers, usually lacks the epistemological component. To consider this component will lead us to a more accurate analysis of the obstacles that a student has to overcome through her/his instruction. Is this paper, Astolfi shows the differences between obstacle and preconception, the three stages to overcome an obstacle, and how to use the concept of objective-obstacle to improve science teaching.